Benchmark Problems for Exhaustive Exact Maximum Clique Search Algorithms - Szabó, Sándor; Zaválnij, Bogdán (Informatica, 2019)
There are well established widely used benchmark tests to assess the performance of practical exact clique search algorithms. In this paper a family of further benchmark problems is proposed mainly to test exhaustive clique search procedures.